2007
DOI: 10.1088/0967-3334/28/10/006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating stroke volume from oxygen pulse during exercise

Abstract: This investigation aimed at verifying whether it was possible to reliably assess stroke volume (SV) during exercise from oxygen pulse (OP) and from a model of arterio-venous oxygen difference (a-vO(2)D) estimation. The model was tested in 15 amateur male cyclists performing an exercise test on a cycle-ergometer consisting of a linear increase of workload up to exhaustion. Starting from the analysis of previous published data, we constructed a model of a-vO(2)D estimation (a-vO(2)D(est)) which predicted that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 40 publications
1
48
1
Order By: Relevance
“…Previous studies have identified a correlation between stroke volume and O 2 pulse during exercise in humans (23,24). increased with increasing Htc values in both groups (Fig.…”
Section: Effect Of Varying Blood Volume Total Hemoglobin Mass Andmentioning
confidence: 55%
“…Previous studies have identified a correlation between stroke volume and O 2 pulse during exercise in humans (23,24). increased with increasing Htc values in both groups (Fig.…”
Section: Effect Of Varying Blood Volume Total Hemoglobin Mass Andmentioning
confidence: 55%
“…Oxygen pulse, a non-invasive marker of stroke volume [12][13][14], was calculated from V9O 2 and cardiac frequency (eC) collected breath-by-breath during the CPET as previously described [22].…”
Section: Oxygen Pulsementioning
confidence: 99%
“…We hypothesised that LVRS would lead to an increase in non-invasive markers of stroke volume (oxygen pulse [12][13][14] and pulse pressure (PP) [15,16]) during exercise and that these improvements would correlate with a reduction in DH.…”
mentioning
confidence: 99%
“…Thus, different investigators using distinct populations and/or clinical and sports settings have proposed that the O 2 pulse can indirectly reflect stroke volume, so that both the maximum value and the curve shape, which are a function of CPET duration, will be directly associated with cardiac inotropism and lusitropism (4)(5)(6)(7)(8)(9)(10). In this context, several studies have shown that relatively low maximum O 2 pulse values are associated with a lower survival rate among middle-aged individuals as well as patients with heart failure (11,12), most likely reflecting impaired inotropic and/or lusitropic capacity and then disturbing the stroke volume response to exercise.…”
mentioning
confidence: 99%